Psychosocial Intervention in Response to COVID-19 Pandemic in Sarawak - Chuong Hock, Ting; Joo Siang, Tan; Wan Xin, Chan; Siok Ping, Voon (Secholian Publication, 2022)
In the wake of the COVID-19 pandemic, the world has been anticipating a greater need for mental health and psychosocial support with the rise in mental health issues when facing many struggles and uncertainties, testing the limits of our current health care system. In this paper, we aim to present a general view of the psychosocial support implemented in Sarawak during the COVID-19 pandemic from the lens of different socio-ecological systems in Sarawak which include the healthcare system, community organizations, and the policy makers. Firstly, this paper provides an overview of the COVID-19 situation in Sarawak in general for the past year. Worth to mention, Sarawak was the first state in Malaysia recorded fatality case resulted from COVID-19 and this inevitably triggered strong negative emotional response during the initial stage of the pandemic. Secondly, the combined efforts initiated by the local state government, the state health departments, several general hospitals and major health clinics were addressed. The delivery of health care service had to be modified according to the strict preventive and social distancing measures recommended by the public health system, including the shift of conventional service to the provision of tele-counselling and psychological first aid. Also, the COVID-19 pandemic and its impact on mental health has brought the politicians’ attention. Lastly, the challenges faced in dealing with the mental health services during the COVID-19 pandemic and the potential paths of the mental health movement were discussed.